2021
DOI: 10.1186/s40479-021-00154-w
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive behaviours in adolescence and their associations with personality traits, emotion dysregulation and other clinical features in a sample of Italian students: a cross-sectional study

Abstract: Background Emotion Dysregulation (ED), childhood trauma and personality are linked to the occurrence of maladaptive behaviours in adolescence which, in turn, may be related to increased risk for psychopathology in the life course. We sought to explore the relationship among the occurrence of different clusters of maladaptive behaviours and ED, clinical features (i.e. impulsivity, childhood maltreatment, anxiety, depressive symptoms) and personality traits that have been found to be associated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…These results can be explained from a psychopathological point of view since patients with binge behaviors (BD and binge eating) have predisposition to act impulsively, with an increase in the likelihood of asocial behaviors, intentional injuries, and suicide attempts. 45 46 In line with other series, CVD was the leading cause of mortality in patients without BD. 47 Our study implies the need to increase awareness and an adequate evaluation of mental health disorders related to alcohol in the setting of bariatric procedures before and after surgery.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results can be explained from a psychopathological point of view since patients with binge behaviors (BD and binge eating) have predisposition to act impulsively, with an increase in the likelihood of asocial behaviors, intentional injuries, and suicide attempts. 45 46 In line with other series, CVD was the leading cause of mortality in patients without BD. 47 Our study implies the need to increase awareness and an adequate evaluation of mental health disorders related to alcohol in the setting of bariatric procedures before and after surgery.…”
Section: Discussionsupporting
confidence: 80%
“…A notable finding is the significantly higher prevalence of suicide in patients with BD compared to other US series of bariatric patients 27 and the general population. These results can be explained from a psychopathological point of view since patients with binge behaviors (BD and binge eating) have predisposition to act impulsively, with an increase in the likelihood of asocial behaviors, intentional injuries, and suicide attempts 45,46 . In line with other series, CVD was the leading cause of mortality in patients without BD 47 .…”
Section: Discussionsupporting
confidence: 71%
“…Despite these slight variations in findings, there is no doubt that the prevalence of NSSI is high worldwide. Adolescence is a sensitive and vulnerable period of time in which a person learns methods of internalizing and externalizing emotions, and a wide range of problematic behaviors can develop as a result of learning unhealthy coping mechanisms ( 77 ). Adolescents who have trouble expressing emotions and feelings may project a depressed mood characterized by impulsive and irritable self-injury and self-mutilation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our sample the UCLA scores were not particularly high, but its effect on mental health status seems to be strong. Furthermore, the link between the occurrence of risky behaviors such as self-harm and binge eating, and poor mental health is well documented [ 41 , 86 ], as well as for gender differences [ 21 , 57 , 84 ]. A recent longitudinal study [ 55 ] including a pre-post pandemic evaluation found that after controlling for baseline mental health status, those adolescents reporting an increase in self-harm, binge-drinking, aggressiveness, and binge-eating were more likely to present a worsened mental health status.…”
Section: Discussionmentioning
confidence: 99%